The Impact of Fiber Density and Layering in NFRP on Confined Concrete Compressive Strength - Zahra Amalia; Taufiq Saidi; Muttaqin Hasan; Nazira Suha Al-Bakri; Li Fu (Journal of the Civil Engineering Forum, 2024)
Strengthening columns holds a crucial role in structural engineering and is frequently called for due to a range of factors, including heightened load requirements, structural degradation, design flaws, or the need for seismic retrofitting. Natural Fiber-Reinforced Polymers (NFRP) in concrete reinforcement has gained significant attention in recent years as a sustainable and eco-friendly alternative to strengthened reinforced concrete. NFRP jacketing presents an adaptable option, as it delivers an improved load-carrying capability as a confining effect. This paper explores the fundamental reasons behind the need for column strengthening and the advantages of employing NFRP jacketing as a preferred method. The study examined the influence of varying fiber densities and the number of fiber layers in NFRP on the mechanical properties of concrete, with a specific focus on its confined concrete compressive strength. The test specimen was a cylinder with a diameter of 150mm and a height of 300mm. NFRP, made from abaca fiber and resin, was attached around the specimen’s circumference to provide a confinement effect. Axial load was applied to the test specimen. The findings indicated that introducing abaca fiber as an NFRP material increased confined concrete compressive strength by up to 37% compared to unconfined concrete. Moreover, the application of three layers of NFRP fibers results in a 15% rise in confined concrete stress, especially when higher-density fiber types are utilized. Study findings suggest that natural fiber density and the number of layers play a role in enhancing concrete strength, however, their influence may not be significantly pronounced.